The Impact of Digital Transformation on Risk-Taking of Commercial Banks in Indonesia - Muhammad Lukman Hakim; Rizal Ahmad Fauzi (Dinasti Publisher, 2025)
Background: Progress in digital technology has prompted commercial banks to undergo digital transformation to improve operational efficiency and consolidate risk management measures. The empirical relationship between bank risk-taking and digital transformation is however inconclusive and subject to contingencies. Purpose: The study aims to examine the effect of digital transformation on credit risk (Non-Performing Loan/NPL), insolvency risk (Z-score), and liquidity risk (Loan-to-Deposit Ratio/LDR) at Indonesian commercial banks during the period from 2014 to 2024. Design/methodology/approach: This study employs the quantitative technique of panel data regression of 10 Indonesian commercial banks. The Analytic Hierarchy Process (AHP) method is also employed to determine the priority between risk indicators affected by digital transformation in order to guarantee methodological triangulation. Findings/Result: The regression result indicates that digital transformation is statistically negatively correlated with credit risk (NPL), although the correlation is not significant at the 5% level. No significant relationship comes out of Z-score and LDR. AHP results identify that NPL has the highest priority weight of 0.7445, indicating that digital transformation activities are primarily focused on mitigating credit risk. Conclusion: Digitalization of Indonesian commercial banks could potentially reduce credit risk but needs further strengthening and testing to obtain statistically significant outcomes. Emphasis on NPL in AHP analysis highlights the strategic importance of credit risk management in digitalization. Originality/value (State of the art): This study contributes to the exceedingly small empirical literature on the impact of digital transformation on risk-taking in emerging banking markets. It combines econometric and decision-making approaches (regression and AHP) for a first-of-its-kind, combined look at the way digital initiatives prioritize different types of banking risks.